2015
DOI: 10.4049/jimmunol.1501702
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Memory T and B Cells in Rhesus Monkeys following Influenza A Infection

Abstract: Studies of influenza-specific immune responses in humans have largely assessed systemic responses involving serum Ab and peripheral blood T cell responses. However, recent evidence indicates that tissue-resident memory T (TRM) cells play an important role in local murine intrapulmonary immunity. Rhesus monkeys were pulmonary exposed to 2009 pandemic H1N1 virus at days 0 and 28 and immune responses in different tissue compartments were measured. All animals were asymptomatic postinfection. Although only minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 67 publications
(76 reference statements)
1
35
0
Order By: Relevance
“…5). Interestingly, some of the human CD3 + T-cell infiltrates appeared to be fairly organized, such those described in the epithelial lung niches of severely-infected mice and humans with influenza viruses [60][61][62][63][64] (Fig. 5E).…”
Section: Sars-cov-2 Infected His-draga Mice Display Human-like Lung Imentioning
confidence: 83%
“…5). Interestingly, some of the human CD3 + T-cell infiltrates appeared to be fairly organized, such those described in the epithelial lung niches of severely-infected mice and humans with influenza viruses [60][61][62][63][64] (Fig. 5E).…”
Section: Sars-cov-2 Infected His-draga Mice Display Human-like Lung Imentioning
confidence: 83%
“…Measurement of IL‐17 and IFN‐γ production in recirculating versus gingiva‐resident memory T cells based on CD69 expression was not possible because in vitro stimulation with SEB leads to CD69 expression on most T cells . We next compared the cytokine response between the memory T cell CD103 + and CD103 − subsets.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of IL-17 and IFN-production in recirculating versus gingiva-resident memory T cells based on CD69 expression was not possible because in vitro stimulation with SEB leads to CD69 expression on most T cells. 29 We next compared the cytokine response between the memory T cell CD103 + and CD103 − subsets. We found that the frequency of CD4 + CD103 + memory T cells that produced IFN-was 4.4-fold higher than that of CD4 + CD103 − memory T cells however, the differences did not reach statistical significance (12.87% ± 4.82% versus 2.92% ± 1.55%; P = 0.06) ( Figure 5B).…”
Section: Il-17 and Ifn-responses From Memory T Cells Isolated From Pementioning
confidence: 99%
“…IgG-secreting plasma cells localized to the lung and peak at 2 weeks, finally resolving the infection. 98,99 Organisms lacking adaptive immunity were shown to have enhanced resistance to subsequent infections (trained immunity). Innate trained immunity occurs in human monocytes and MØ; mTOR/Akt/PI3K-regulated metabolic reprogramming, including increased glutamine metabolism, a shift from OXPHOS-to-aerobic glycolysis, and cholesterol synthesis contribute to this process.…”
Section: Igg2a and Other Isotypes Are Largely Th-dependent And Occurmentioning
confidence: 99%